Highlights in IBD Epidemiology and Its Natural History in the Paediatric Age - Marco Gasparetto; Graziella Guariso (Gastroenterology Research and Practice)
Background. The number of patients of all age brackets diagnosed with Inflammatory Bowel Disease (IBD) has risen dramatically worldwide over the past 50 years. IBD’s changing epidemiology suggests that environmental factors play a major role in modifying disease expression. Aim. To review studies carried out worldwide analyzing IBD epidemiology. Methods. A Medline search indicating as keywords “Inflammatory Bowel Disease,” “epidemiology,” “natural history,” “Crohn’s Disease,” “Ulcerative Colitis,” and “IBD Unclassified” was performed. A selection of clinical cohort and systematic review studies that were carried out between 2002 and 2013 was reviewed. Studies referring to an earlier date were also considered whenever the data were relevant to our review. Results. The current mean prevalence of IBD in the total population of Western countries is estimated at 1/1,000. The highest prevalence and incidence rates of IBD worldwide are reported from Canada. Just as urbanization and socioeconomic development, the incidence of IBD is rising in China. Conclusions. Multicenter national registers and international networks can provide information on IBD epidemiology and lead to hypotheses about its causes and possible management strategies. The rising trend in the disease’s incidence in developing nations suggests that its epidemiological evolution is linked to industrialization and modern Westernized lifestyles.